Determinants of incident chronic kidney disease and progression in a cohort of HIV‐infected persons with unrestricted access to health care1. Issue 2 (19th July 2012) - Ganesan, A; Krantz, EM; Huppler Hullsiek, K; Riddle, MS; Weintrob, AC; Lalani, T; Okulicz, JF; Landrum, M; Agan, B; Whitman, TJ; Ross, MJ; Crum‐Cianflone, NF; et al.
Abstract : Objectives: As socioeconomic factors may impact the risk of chronic kidney disease (CKD), we evaluated the incidence and risk factors of incident CKD among an HIV‐infected cohort with universal access to health care and minimal injecting drug use (IDU). Methods: Incident CKD was defined as an estimated glomerular filteration rate (eGFR) <60 ml/min/1.73 m 2 for ≥ 90 days. eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equation. Rates were calculated per 1000 person‐years (PY). Associations with outcomes were assessed using two separate Cox proportional hazard models, adjusting for baseline and time‐updated covariates. Results: Among 3360 participants [median age 29 years; 92% male; 44% African American (AA)] contributing 23 091 PY of follow‐up, 116 developed incident CKD [5.0/1000 PY; 95% confidence interval (CI) 4.2–6.0/1000 PY]. The median first eGFR value was 97.0 mL/min/1.73 m 2 [interquartile range (IQR) 85.3–110.1 mL/min/1.73 m 2 ]. Baseline factors associated with CKD included older age, lower CD4 count at HIV diagnosis [compared with CD4 count ≥ 500 cells/μL, hazard ratio (HR) 2.1 (95% CI 1.2–3.8) for CD4 count 350–499 cells/μL; HR 3.6 (95% CI 2.0–6.3) for CD4 count 201–349 cells/μL; HR 4.3 (95% CI 2.0–9.4) for CD4 count ≤ 200 cells/μL], and HIV diagnosis in the pre‐highly active antiretroviral therapy (HAART) era. In the time‐updated model, low nadir CD4 counts, diabetes, hepatitis B, hypertension and less HAART use were also associated with CKD. AA ethnicity was not associated with incident CKD in either model. Conclusions: The low incidence of CKD and the lack of association with ethnicity observed in this study may in part be attributable to unique features of our cohort such as younger age, early HIV diagnosis, minimal IDU, and unrestricted access to care. Lower baseline CD4 counts were significantly associated with incident CKD, suggesting early HIV diagnosis and timely introduction of HAART may reduce the burden of CKD.